Task Tours: Helping Users Tackle Complex Search Tasks - Awadallah, Ahmed; White, Ryen W. (CIKM '12 Proceedings of the 21st ACM international conference on Information and knowledge management, 2012)
Complex search tasks such as planning a vacation often comprise multiple queries and may span a number of search sessions. When engaged in such tasks, users may require holistic support in determining the required task activities. Unfortunately, current search engines do not offer such support to their users. In this paper, we propose methods to automatically generate task tours comprising a starting task and a set of relevant related tasks, some or all of which may be necessary to satisfy a user's information needs. Applications of the tours include helping users understand the required steps to complete a task, finding URLs related to the active task, and alerting users to activities they may have missed. We demonstrate through experimentation with human judges and large-scale search logs that our tours are of good quality and can benefit a significant fraction of search engine users.